Organometallic Reactions and Polymerization - Osakada, Kohtaro (Lecture Notes in Chemistry, 2014)
This compilation provides advanced graduate students and researchers with a structured overview of olefin polymerization. Divided into eight chapters written by international experts, this book covers polymerization using various organotransition-metal catalysts, including early and late transition metal complexes, new trends in olefin oligomerization and related reactions. All authors address the historic and scientific backgrounds of the field as well as current research progress and potential for further research. The complete book is designed to present eight independent lectures and, because all authors are well versed in organometallic chemistry, each is based on a profound understanding of the reactions and structures of organotransition metal complexes. This book is an ideal accompaniment for researchers taking courses in olefin polymerization and also serves as a valuable resource for teachers and lecturers of chemistry when planning and researching material for advanced lecture courses.